Acoustic scattering properties of seagrass: In/ex-situ measurements of Posidonia oceanica - MUTLU, ERHAN; Olguner, Cansu (Mediterranean Marine Science, 2023)
The marine prairies are paramount to the marine ecosystem playing a crucial role in various ways. Owing to the global atmospheric events inducing hydrospheric changes, marine seaweeds have been negatively affected and are vulnerable. Conventional methods (SCUBA), which were previously used to collect seagrasses, have become a destructive method for deriving unrecoverable damages for their stocks and have been replaced with remote sensing methods. Considering the advantages of the acoustic methods, two different in/ex-situ experiments were conducted to ground-truth the common seagrass, P. oceanica, in time and space of the Turkish Mediterranean water in 2011-2012 using a scientific echosounder with a split beam transducer operated at a frequency of 206 kHz. After the separation of the seagrass from spurious scatterers, the acoustic parameters (Sa: area backscattering strength, Sv: volume backscattering strength, and TS: Target Strength) were correlated and regressed with the biometric variables (Leaf Area Index, biomass, volume, length, width, diameter, or thickness) of different parts (leaf, rhizome, and sheath) of the seagrass. Estimation of biometrics by acoustic methods has been considered a challenge up to now. Statistical relationships between biometrics and acoustics were precisely examined for the species. The relationships were linearly established in the acoustic geometric region. There was a seasonal difference in the relationships. Their rhizomes and sheaths were considered unstable non-linear parts and remained unexplained for the acoustic response. Acoustic response to the leaf density (d, g cm-3), which was a distinguished component in the reflection, was found to be dependent on the seasonal biological activities of P. oceanica. Posidonia, which has a d greater than 1 g/cm3, produced the geometric region. The present study was the first attempt to establish the relationships of the seagrass under protection, and can decrease usage of destructive methods for future studies.